2016
DOI: 10.1111/avsc.12264
|View full text |Cite
|
Sign up to set email alerts
|

Restoration over time: is it possible to restore trees and non‐trees in high‐diversity forests?

Abstract: Questions Do different growth forms have distinct temporal patterns of recovery of their structure, diversity, and composition in restored Atlantic Rain forest? Are tree and non‐tree assemblages structured by the same factors? Location Atlantic Rain Forest, restored by planting an assemblage of high‐diversity tree species, Brazil. Methods We measured plant colonization of restoration sites of different ages to evaluate restoration success in terms of species diversity, colonization by non‐tree species and stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 70 publications
2
33
1
1
Order By: Relevance
“…As restoration sites mature, microsite limitations may be modulated, which facilitates more seedling colonization in older than younger sites (Bertacchi et al 2016), implying that microsites are a stronger limiting factor to seedling colonization in younger than older sites. The progressive increase of diversity and richness with age shown by this study, and other ecosystem components such as trees (Garcia et al 2016), arthropods (Nyafwono et al 2014) reported in previous studies highlight the biodiversity benefits of continued management of restored forests.…”
Section: Effect Of Sampling Year Restoration Age and Distance From supporting
confidence: 77%
“…As restoration sites mature, microsite limitations may be modulated, which facilitates more seedling colonization in older than younger sites (Bertacchi et al 2016), implying that microsites are a stronger limiting factor to seedling colonization in younger than older sites. The progressive increase of diversity and richness with age shown by this study, and other ecosystem components such as trees (Garcia et al 2016), arthropods (Nyafwono et al 2014) reported in previous studies highlight the biodiversity benefits of continued management of restored forests.…”
Section: Effect Of Sampling Year Restoration Age and Distance From supporting
confidence: 77%
“…Furthermore, the restoration species pool constituted a narrow spectrum of growth forms that lack or underrepresent lianas, epiphytes, and herbs. Likewise, other studies regarding plant nursery diversity in tropical regions (specifically in Panama, Philippines, and Mexico) (Román et al 2012;Gregorio et al 2017;Ramírez-Soto et al 2018) confirmed the bias toward tree species, despite the relevant role these growth forms play in ecological restoration (Campbell et al 2015;Garcia et al 2016;Mayfield 2016). This fact reinforces the practical gaps related to the restoration of nonforest ecosystems in the tropics, where restoration demand is increasing and propagation knowledge is lacking (Overbeck et al 2013;Veldman et al 2015).…”
Section: Discussionmentioning
confidence: 78%
“…Eucalyptus species), or reflect biases in tubestock availability. Biased patterns of growth‐form recovery have been commonly observed in active restoration of other vegetation types (Munro et al ; Nichols et al ; Garcia et al ). Our results suggest that, when mature, vegetation structure in plantings may be less complex than remnant stands, which has been shown to reduce the maximum carbon that can be stored as woody biomass (Ford & Keeton ).…”
Section: Discussionmentioning
confidence: 97%